Efcacy of Electrostimulation and Pelvic Floor Muscle Exercises in the Treatment of Stress Urinary Incontinence in Women: Randomised Controlled Trial - Vaiva Nepaitė-Stabingė; Anelė Katinė; Erika Karkauskienė; Vilma Dudonienė (Lithuanian Sports University, 2023)
Background. Pelvic ﬂoor muscle training (PFMT) is the most commonly used physiotherapy method in the treatment of female stress incontinence; pelvic ﬂoor muscles (PFM) can be trained not only with exercise but also with electrostimulation. The aim. To determine the efcacy of four weeks of pelvic ﬂoor muscle exercises and electrical stimulation in the treatment of stress urinary incontinence in women. Methods. The study involved 24 subjects who were randomly divided into two groups: pelvic ﬂoor muscle training (PFMT) and pelvic ﬂoor muscle exercises combined with electrostimulation (PFMES). Before and after the interventions, women's quality of life (QoL) was assessed according to the International Incontinence Counselling Questionnaire - Short Form. Perineometry with Pelvexiser perineometer was used to measure pelvic ﬂoor muscle strength, endurance and vaginal resting pressure. Results. Both interventions signifcantly reduced urinary incontinence episodes and improved the subjects' quality of life. PFM strength improved after the interventions in the PFMT group from 12.33±3.37 to 19.97±3.38 mmHg (p=0.0008, d=2.26) and in the PFMES group from 8.31±2.41 to 11.84 ±2.78 mmHg (p=0.003, d=2.6). PFM endurance improved in the PFMT group from 3.50±1.15 to 4.53±1.12 s (p=0.03, d=0.9), and in PFMES from 2.92±0.47 to 3.67±0, 52 s (p=0.001, d=1.45). Resting vaginal pressure in the PFMT group improved from 5.3±0.85 to 6.44±1.03 mmHg (p=0.005, d=1.25) and in the PFMES group from 4.4±0.70 to 6.14± 1.47 mmHg (p=0.001, d=1.5). Conclusions. PFMT and PFMES interventions signifcantly improved subjects' PMF strength, endurance, resting vaginal pressure, and quality of life. Both applied interventions can be applied in the treatment of stress urinary incontinence, as they were safe and well tolerated by the patients. The trial is registered at ClinicalTrials.gov Identifer: NCT05871281. Keywords: female, strength, endurance, incontinence, questionnaire.